2019
DOI: 10.1007/s12264-019-00423-3
|View full text |Cite
|
Sign up to set email alerts
|

Rabies Virus Pseudotyped with CVS-N2C Glycoprotein as a Powerful Tool for Retrograde Neuronal Network Tracing

Abstract: Background: Efficient viral vectors for mapping and manipulating long projection neuronal circuits are crucial in brain structural and functional studies. The glycoprotein gene-deleted SAD strain rabies virus pseudotyped with the N2C glycoprotein (SAD-RV(ΔG)-N2C(G)) shows high neuro-tropism in cell culture, but its in vivo retrograde infection efficiency and neuro-tropism have not been systematically characterized. Methods: SAD-RV(ΔG)-N2C(G) and two other broadly used retrograde tracers, SAD-RV(ΔG)-B19(G) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 72 publications
(71 reference statements)
1
31
0
Order By: Relevance
“…The stereotactic coordinates for VTA were: AP: -3.20 mm; ML: ± 0.45 mm; DV: -4.30 mm from the bregma; For CPu: AP: +0.38 mm; ML: ±2.00 mm; DV: -3.50 mm from the bregma. 8-10 weeks old C57BL/6 mice (20-25 g) were used for aav virus injection, and standard injection process was referred to previously reported method [11]. For single VTA site injection, mice were divided into two groups (N=3 in each group), 300 nl of rAAV2-Retro-CaMKIIa-EGFP, and rAAV9-Retro-CaMKIIa-EGFP viruses were infused into the VTA of each group, respectively; For mixed viral injection into VTA, rAAV2-Retro-CaMKIIa-mCherry and rAAV9-Retro-CaMKIIa-EGFP viruses were mixed at the particles ratio of 1:1 and injected into VTA at 300 nl; For single CPu site injection, mice were divided into two groups (N=3 in each group), 300 nl of rAAV2-Retro-CaMKIIa-EGFP and rAAV9-Retro-CaMKIIa-EGFP viruses were infused into the CPu region of each group, respectively.…”
Section: Administration Of Aav Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The stereotactic coordinates for VTA were: AP: -3.20 mm; ML: ± 0.45 mm; DV: -4.30 mm from the bregma; For CPu: AP: +0.38 mm; ML: ±2.00 mm; DV: -3.50 mm from the bregma. 8-10 weeks old C57BL/6 mice (20-25 g) were used for aav virus injection, and standard injection process was referred to previously reported method [11]. For single VTA site injection, mice were divided into two groups (N=3 in each group), 300 nl of rAAV2-Retro-CaMKIIa-EGFP, and rAAV9-Retro-CaMKIIa-EGFP viruses were infused into the VTA of each group, respectively; For mixed viral injection into VTA, rAAV2-Retro-CaMKIIa-mCherry and rAAV9-Retro-CaMKIIa-EGFP viruses were mixed at the particles ratio of 1:1 and injected into VTA at 300 nl; For single CPu site injection, mice were divided into two groups (N=3 in each group), 300 nl of rAAV2-Retro-CaMKIIa-EGFP and rAAV9-Retro-CaMKIIa-EGFP viruses were infused into the CPu region of each group, respectively.…”
Section: Administration Of Aav Particlesmentioning
confidence: 99%
“…Viral vectors, especially which permit e cient gene transfer to central nervous system (CNS) from axonal terminals or across the blood-brain barrier, are useful for analyzing structure and function of speci c neuronal circuits around the injection site [1][2][3][4][5][6][7][8][9][10][11], and have become one of the most potential and promising therapy tools by delivery therapeutic genes to a distant target area [5,12]. Compared with traditional retrograde tracers, viral vectors can express genes in speci c neuron groups [9,13], and have been widely used to monitor and manipulate neuronal activities by expressing optogenetic [14,15], chemogenetic [16,17] and calcium-sensitive functional probes [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In the present issue of Neuroscience Bulletin, Zhu and collaborators [8] compared the efficiency of retrograde gene transduction and neurotropism in three widely-used retrograde virus tracers. They found that the SAD strain of rabies virus [SAD-RV(DG)-N2C(G)], packaged with the N2C glycoprotein from the CVS strain [9], has a retrograde efficiency comparable to rAAV2-retro, but has a broader tropism in different neural types and regions, especially in subcortical regions.…”
mentioning
confidence: 99%
“…They found that the SAD strain of rabies virus [SAD-RV(DG)-N2C(G)], packaged with the N2C glycoprotein from the CVS strain [9], has a retrograde efficiency comparable to rAAV2-retro, but has a broader tropism in different neural types and regions, especially in subcortical regions. However, rAAV2-retro is more suitable for cortical neural circuit tracing [8]. On the other hand, HSV1 strain H129, widely used as an anterograde tracer, also efficiently infects upstream innervating neurons through axon terminal uptake and displays a clear retrograde labeling phenotype, indicating that there are two types of starter cell: locally infected neurons in the injection site and retrogradely infected neurons [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation